The perils of a persistent cough. Issue 2 (June 2020) - Fox, Natalya; Ranmuthu, Sajeev; Periselneris, Jimstan; Hardavella, Georgia
A 66-year-old, female, lifelong nonsmoker was referred to the chest clinic on an urgent referral pathway. She presented with dry cough and breathlessness of 6 months duration on a background of intermittent cough for 5 years. She had no sputum production, haemoptysis or weight loss, and maintained a good appetite. The cough was triggered by perfumes/allergens. Her medical history was unremarkable and she denied hay fever or gastro-oesophageal reflux-like symptoms. Family history included asthma and eczema. Her father had been a heavy smoker who died of lung cancer; therefore, there had been passive exposure to smoking. Always consider an underlying diagnosis of Aspergillus -related disease when faced with persistent symptoms in an individual with predisposing risk factors ( e.g. asthma) http://bit.ly/3aBTQip